Integrating the technical, risk management and economic implications of animal disease control to advise policy change: The example of foot-and-mouth disease control in Uruguay - Perry, Brian D.; Rich, Karl M.; Rojas, H.; Romero, J.; Adamson, D.; Bervejillo, J.E.; Fernandez, F.; Pereira, A.; Pérez, L.; Reich, F.; Sarno, R.; Vitale, E.; et al. (Springer, 2020)
Countries contemplating a change in their animal disease control policy face a variety of considerations, particularly in circumstances in which disease status, and the use (or not) of vaccines to control or minimise disease risk, has major implications for international trade. Foot-and-mouth disease (FMD) exemplifies these trade-offs, and is particularly important in South America, where FMD virus circulation has declined and appears limited to certain regions. As a result, opportunities for higher-value exports in sustainably produced pasture-fed beef and lamb are growing. Uruguay is arguably at the forefront of these developments. It is renowned for an efficient livestock production base, high standards of animal health, and a pasture-based, extensive feeding system. Uruguay exports over four per cent of the world’s fresh and frozen meat (https://oec.world/en/profile/country/ury/), and in 2018, 70% of these exports went to China (Joseph 2019). Parts of neighbouring countries such as Brazil, Argentina and Paraguay share the advantages of pasture-based feeding, and also aspire to sell to more diverse international markets. Export market access for all these countries depends on the successful control of FMD. A country’s FMD status (whether endemic, free with vaccination, or free without vaccination) has implications for market access and prices, and these depend on trading partners’ willingness to accept different levels of risk. Some of the highest value markets for beef, such as Japan and Korea, only allow imports from the very small subset of countries that are FMD-free without vaccination against FMD (Rich and Winter-Nelson 2007). Uruguay and its neighbours are contemplating new FMD policy measures, including the cessation of blanket vaccination, in order to improve the quality, quantity and diversity of their markets. This will also contribute to the broader hemispheric aspirations of PHEFA (Hemispheric Foot and Mouth Disease Control Programme 2011–2020), together with the countries of South America and Panama, to eradicate FMD under the coordination of PANAFTOSA.Footnote1 In May 2019, the Uruguayan Ministry of Livestock, Agriculture and Fisheries (MGAP), the Instituto Nacional de Investigación Agropecuaria (INIA), and the Instituto Nacional de Carnes (INAC) jointly commissioned an independent evaluation of the implications of moving to a no FMD vaccination policy in the country, and to assess the technical, risk management and economic implications of any such change. The authors undertook this study, and in-country meetings and workshops were conducted in May, June, August and October 2019. Here, we present the study results and the broader implications of such interdisciplinary team studies to underlie animal health policy change in other counties and for other trade-related diseases.